OBSERVATIONS AND A NEW SPECIES IN THE GENUS PSEUDOPYXIS (RUBIACEAE) - Chen, Tao (Edinburgh Journal of Botany, 2007)
Specimens of Pseudopyxis Miq. (Rubiaceae) from China and Japan were studied and compared. As the plants from China differ considerably from those from Japan a new species, Pseudopyxis monilirhizoma T.Chen, is described and a key to Pseudopyxis is presented.
Keywords: China; East Asia; Pseudopyxis; Pseudopyxis monilirhizoma; Rubiaceae